THE EFFECT OF AUTOCRATIC LEADERSHIP STYLE AND EMPLOYEE WORK STRESS ON TURNOVER INTENSITY AT PERDADANI NASIONAL MADANI LIMITED LIABILITY COMPANY, PEKANBARU - Fernanda Arifin, Robby; Yuni Pratikno; Hadi Mulyo Wibowo (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2025)
The purpose of this study is to find out the influence of autocratic leadership style on turnover intensity, find out the effect of employee work stress on turnover intensity, and find out the influence of autocratic leadership style and employee work stress on turnover intensity. This research has a quantitative approach. In the autocratic leadership style variable (X1) the calculated t value is 7,128 > the t value of the table is 1,988. With the significance value of 0.001, which is less than 0.5 or 0.00 < 0.05. So it can be concluded that Ha is accepted and H0 is rejected, which means that the autocratic leadership style partially has an influence on the Turnover Intensity of the Madani National Capital Limited Liability Company Pekanbaru Branch. In the employee work stress variable (X2) the calculated t value is -0,838 < the table t value is 1,988, with the significance value -0,071. So it can be concluded that Ha is rejected and H0 is accepted, which means that employee work stress partially has no effect on Turnover Intensity at Madani National Capital Limited Liability Company Pekanbaru Branch. F count (25,701) > F table (3,949) with Sig. (0,001) < 0.05. It means that the variables of autocratic leadership style and employee work stress simultaneously have a significant effect on Turnover Intensity.